Paul Hindemith travel in Argentina (Revista del Instituto de Investigación Musicológica "Carlos Vega", 2017)
In 1954 Paul Hindemith arrived in Argentina, where he remained for two months performing a great number of concerts in Buenos Aires and Mendoza, with works of universal repertoire (especially Ancient music) and his own works, most of them in first audition. Although some authors mention this tour, none has detailed the activities of this German musician and his relationship with the “Asociación Amigos de la Música”, for which he was invited. This association, created in 1946 by a group of people (musicians, architects, etc.) exiled during Nazism, created the possible links for their journey. The information to know the tour of the activities of Hindemith in the country, I found it looking in periodical publications of the time fundamentally in the hemerographic collection that keeps the Biblioteca Nacional “Mariano Moreno”, photographs from the Archive Julio Perceval that belongs to Universidad Nacional de Cuyo and the private archive of Carlos GrÁ¤tzer. This article relates in detail to its passage through this country, includes photographs - some unpublished - and a copy of a manuscript score - also unpublished - of the German composer
Keywords: Hindemith; Asociación Amigos de la Música; Guillermo Graetzer; Julio Perceval